Amorphous Co‐P Film: an Efficient Electrocatalyst for Hydrogen Evolution Reaction in Alkaline Seawater. Issue 7 (30th December 2022) - Liang, Yimei; Zhang, Longcheng; Liu, Qin; Ouyang, Ling; Luo, Yongsong; Zheng, Dongdong; Wang, Yan; Sun, Shengjun; Wang, Xiangguo; Zhang, Jing; Xu, Chenggang; Sun, Xuping
Abstract: Seawater electrolysis is considered an attractive alternative to conventional freshwater electrolysis for hydrogen production due to the abundance of seawater in nature. For this reason, efficient electrocatalysts for hydrogen evolution reaction (HER) in alkaline seawater are highly desired. In this study, we report an amorphous Co−P alloy on nickel foam (Co−P/NF) that behaves as an efficient and stable HER electrocatalyst for alkaline seawater electrolysis. The Co−P/NF presents high catalytic performance for HER, requiring a low overpotential of 213 mV to drive a current density of 100 mA cm −2 and a Tafel slope of 120.2 mV dec −1 in alkaline seawater. Furthermore, it shows remarkable electrochemical and structural stability in alkaline seawater. Abstract : Amorphous Co−P alloy on nickel foam exhibits high hydrogen‐evolving performance, requiring overpotentials of 170 and 213 mV to deliver a current density of 100 mA cm −2 in alkaline freshwater and alkaline seawater, respectively.